2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627778
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and interpretable model for BCCT.core

Abstract: Abstract-Breast Cancer Conservative Treatment (BCCT) is considered nowadays to be the most widespread form of locorregional breast cancer treatment. However, aesthetic results are heterogeneous and difficult to evaluate in a standardized way. The limited reproducibility of subjective aesthetic evaluation in BCCT motivated the research towards objective methods. A recent computer system (BCCT.core) was developed to objectively and automatically evaluate the aesthetic result of BCCT. The system is centered on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
(13 reference statements)
0
22
0
2
Order By: Relevance
“…Results are classified automatically as excellent, good, fair, and poor. 11,13 Despite the fact that it was designed for breast-conserving treatment evaluation, one study found a statistically significant correlation between the BCCT. core and the Harris Scale for measuring aesthetic outcomes in unilateral breast reconstruction after mastectomy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Results are classified automatically as excellent, good, fair, and poor. 11,13 Despite the fact that it was designed for breast-conserving treatment evaluation, one study found a statistically significant correlation between the BCCT. core and the Harris Scale for measuring aesthetic outcomes in unilateral breast reconstruction after mastectomy.…”
Section: Discussionmentioning
confidence: 93%
“…The final results were displayed by means of a four-point scale: excellent, good, fair, and poor. [11][12][13] To evaluate quality-of-life, all patients answered the BREAST-Q questionnaires, which were previously validated for application in Brazilian patients. 14 The BREAST-Q patient-reported outcome instrument breast reconstruction postoperative module comprises two domains: satisfaction domains (i.e., satisfaction with breasts, satisfaction with outcomes, and satisfaction with care) and quality-of-life domains (psychosocial well-being, physical well-being, and sexual well-being), which consist of nine scales.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [8], an accurate and interpretable model for the BeeT.core was found. The objective of that work was to compare between the previous model used on the evalu ation of the overall aesthetic result of the BeeT [6], with other methods in order to overcome the non-interpretability of the older one.…”
Section: Bcctcore Designmentioning
confidence: 95%
“…1), selecting the aspects with most impact to the overall cosmetic result: breast asymmetry, skin colour changes due to the radiotherapy treatment and surgical scar appearance. Posteriorly, a Support Vector Machine (SVM) classifier was trained to predict the overall cosmetic result from the recorded features [6], [8]. BeeT.core classifies the aesthetic outcome of BeeT into excellent, good, fair, and poor classes.…”
Section: Bcctcore Designmentioning
confidence: 99%
“…The selection of 2D features was based on previous studies Oliveira et al 2010), whereas the 3D features were those presented in this work. The model was designed using the selected features, considering all the possible subsets, using a leave-one-out scheme (Duda et al 2000).…”
Section: Aesthetic Evaluationmentioning
confidence: 99%